2016
DOI: 10.1007/s40261-016-0376-0
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 Diabetes Patients Reach Target Glycemic Control Faster Using IDegLira than Either Insulin Degludec or Liraglutide Given Alone

Abstract: Background and ObjectivesThe time-course when changes in glycemic control and body weight were first manifest in patients with type 2 diabetes mellitus (T2DM) treated with a combination of insulin degludec and liraglutide (IDegLira) was assessed, comparing IDegLira to its individual components.MethodsData from weeks 0–12 from two studies were analyzed, one comparing IDegLira to each component (DUAL I), and one comparing IDegLira to insulin degludec titrated to a maximum 50 units (DUAL II). Efficacy endpoints i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 31 publications
2
7
0
Order By: Relevance
“…Furthermore, the improvement in HbA 1c in the Swiss patients was detectable at approximately 12 weeks (Fig. 1a), which is consistent with data from randomized clinical trials [22]. Unfortunately, as there were no observations in the period between switching to IDegLira and 12 weeks, it is not possible to determine precisely when the decrease began.…”
Section: Discussionsupporting
confidence: 81%
“…Furthermore, the improvement in HbA 1c in the Swiss patients was detectable at approximately 12 weeks (Fig. 1a), which is consistent with data from randomized clinical trials [22]. Unfortunately, as there were no observations in the period between switching to IDegLira and 12 weeks, it is not possible to determine precisely when the decrease began.…”
Section: Discussionsupporting
confidence: 81%
“…Indeed, similar results to those reported in the present paper were observed with IDegLira, an FRC of insulin degludec and the long‐acting GLP‐1RA liraglutide. In a post hoc analysis, IDegLira reduced plasma glucose faster and to a greater extent than its components within the first 12 weeks of therapy, without weight gain or an increased risk of hypoglycaemia . Together, these results support the hypothesis that FRCs allow patients with T2D to achieve glycaemic targets earlier than with insulin alone.…”
Section: Discussionsupporting
confidence: 54%
“…However, mean A1C was ≤7% at end of trial regardless of baseline A1C category for IDegLira (≤7.5, >7.5 to ≤8.5, >8.5 to ≤9.0%, and >9%) and iGlarLixi (<8% and ≥8%) (47,48). Another post-hoc analysis demonstrated that, for IDegLira, the decrease in A1C was measurable within the first 12 weeks of therapy, without weight gain or increased rate of hypoglycemia (49). A post-hoc analysis of the LixiLan-O and LixiLan-L trials (the latter including insulin-experienced patients), published in abstract form, has indicated that iGlarLixi is associated with less glycemic variability than insulin glargine U100 or lixisenatide alone (50).…”
Section: Efficacy Results In the Trialsmentioning
confidence: 99%